Neuroprotective Action of Teriflunomide in a Mouse Model of Transient Middle Cerebral Artery Occlusion. (21st January 2020) - Lu, Zhengfang; Zhang, Di; Cui, Kefei; Fu, Xiaojie; Man, Jiang; Lu, Hong; Yu, Lie; Gao, Yufeng; Liu, Xianliang; Liao, Linghui; Li, Xiang; Liu, Chang; et al.
Highlights: Teriflunomide exhibits protective effects on a mouse model of transient middle artery occlusion. Teriflunomide inhibits neuroinflammation after ischemic stroke. Teriflunomide alleviates blood–brain barrier leakage. Teriflunomide enhances subventricular zone neurogenesis after ischemic stroke. Abstract: Teriflunomide has been reported to inhibit microglial activation in experimental models of traumatic brain injury. However, its roles in ischemic stroke and underlying mechanisms of action are still undiscovered. In this study, we investigated the effects of teriflunomide on brain edema, neurologic deficits, infarct volume, neuroinflammation, blood–brain barrier (BBB) permeability, and neurogenesis in a mouse model of transient middle cerebral artery occlusion (tMCAO). tMCAO mice treated with teriflunomide showed lower brain water content on day 3, milder neurologic deficits and smaller infarct volume on day 7 than those treated with vehicle. Additionally, mice received teriflunomide had fewer activated Iba-1-positive microglia and lower protein levels of interleukin-1β (IL-1β), cyclooxygenase-2 (COX-2), and 3-Nitrotyrosine (3-NT) compared with those received vehicle on day 3. Further, teriflunomide alleviated Evans blue dye leakage, increased pericyte coverage and protein levels of platelet-derived growth factor B (PDGFB), platelet-derived growth factor receptor β (PDGFRβ) and Bcl2, and decreased the number of PDGFRβ/matrix metalloproteinase 9 (MMP9)-positive cells. Moreover, teriflunomide reduced the loss of zonula occludens-1 (ZO-1) and occludin. Finally, teriflunomide significantly upregulated the number of 5-bromo-20-deoxyuridine (BrdU)/doublecortin (DCX)-positive cells and expression of mammalian achaete-scute homolog 1 (Mash1), DCX and Pbx1 in subventricular zone (SVZ) on day 7 after stroke. Our results indicate that teriflunomide exhibits protective roles in ischemic stroke by inhibiting neuroinflammation, alleviating BBB disruption and enhancing neurogenesis.